FREQUENCY OF ENTEROBACTERIA IN FRESH VEGETABLES OF RAW CONSUMPTION SOLD IN FOUR MARKETS IN LIMA, PERU - Muñoz J., Silvia (2013)
The purpose of this study was to evaluate the degree of faecal contamination in three vegetables of major raw consumption that are sold in four large wholesale markets in Lima, Peru. A total of 180 samples, 15 lettuce (Lactuca sativa), 15 cabbage (Brassica oleracea) and 15 spinach (Spinacea oleracea) from La Parada, Ramón Castilla, Ceres and Caquetá markets were collected within a year. Samples were processed using the Most Probable Number method for faecal coliform and E. coli Type I (Typical) detection and count, plus the Absence/Presence test for Salmonella. In the study, 18.9% of all vegetables and 22.2% of vegetables from La Parada market had faecal coliform levels higher than those established by the International Commission on Microbiological Specifications for Foods (ICMSF). In addition, 2.2% vegetables from Caquetá market had high levels of E. coli Type I (Typical), where spinach showed the highest contamination. Ten percent of vegetables had Salmonella spp, where cabbage had the highest levels.